Sistema web de reservación y consulta de exámenes médicos en el laboratorio clínico bacteriológico sedilab de la ciudad de Calceta - Alcívar Macías, José Luis (2013)
The purpose of this work was of developing a system to facilitate the reservation processes and consultation of medical tests in the bacteriological clinical laboratory SEDILAB. For this it was necessary know the techniques that were carried out in the respective department of the mentioned institution, since through an observation of the obtained information it was verified that this processes were carried out in a manual way, registering the data in paper leaves. To fulfill the outlined objectives it was necessary apply methods like the inductive one - deductive, since these allowed to observe how they were carried out the consultation processes in this establishment, the methodology was also used MIDAS for the elaboration of the system web for phases, facilitating its understanding and obtaining an appropriate control of the same one, obtaining the requirements of the software, developing the static part, designing the database and applying the functionality to the system. They were also used technical and instruments like the field observation, the same one that allowed define the necessary data to develop this work; and the interview, thanks to which one could obtain the requirements and to qualify the existent readiness. Programs like PHP were used, MySQL, Wamp Server, Adove Dreamweaver CS3, CS5 and Filezilla to develop the software. Once concluded the application the necessary tests were made to check the correct operation of the system, obtaining the reduction of time as a result in the mentioned processes, concluding that the elaboration of the application web helped considerably so much to employees as clients of the institution.